The Dirichlet problem successive upper relaxation numerical method convergence relaxation parameters influence investigations - Oliynyk, A.P.; Shtayer, L.O. (Carpathian Mathematical Publications, 2012)
The relaxation parameters values to definite sequential upper relaxation block method convergence optimal velocity have been determined for the Dirichlet's problem in two-dimensional rectangle spatial region, the iteration procedure convergence and positive definiteness of the corresponding linear algebraic equations system matrix have been proved.